On the design of rainwater harvesting and greywater recycling systems for urban areas (2017)
Rainwater harvesting is the process of collecting storing, and distributing rainwater for reuse, rather than allowing it to run off. Greywater recycling consists of purifying processes that remove contaminants present in wastewater coming from faucets, showers baths clothes washing, and dishwashing, so that it can be reused, instead of becoming inlet wastewater for municipal wastewater treatment plants. In urban areas, rainwater harvesting and greywater recycling systems provide additional water supplies for houses, buildings, and industries, and also help to mitigate flooding events and pollution. To design an integrated system that includes rainwater harwesting and greywater recycling in residential units, this paper proposes: 1) a multi-objective optimization model that minimizes: potable water consumption, maintenance and operational costs plus potable water cost, and construction costs; and 2) a two-stage stochastic optmization model that incorporates the uncertainty associated with rainfall events. To evaluate the applicability of the proposed optimization models a case study in the city of Soacha in Colombia is presented. The results show a reduction of more than 30% of the potable water consumed.